Kesiapan UMKM Menghadapi Redenominasi Rupiah dalam Ekosistem Pembayaran Digital QRIS - Sovie Sri Anggraeni; Erna Nur Fadhilah; Theresia Linda Verlita; Shofi Nurhasna Fatin (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This research analyzes the readiness of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia to face the potential implementation of the rupiah redenomination policy, focusing on digital payment transformation and QRIS adoption as the main payment system. The qualitative method involved interviews with MSME actors, consumer surveys, and comprehensive document studies combining data from regulations, reports, and scientific articles. The main findings reveal challenges such as varying levels of understanding about redenomination, difficulties in financial records and price adjustment, and technical issues within payment systems. Consumers require price clarity and protection against transaction errors and fraud during the transition. Most MSMEs have adopted non-cash payments, mainly using QRIS, yet still need educational support and infrastructure improvements. This study develops an empirical readiness framework for MSMEs consisting of four core pillars: (1) Technology and System Readiness, including digital infrastructure modernization and device subsidies; (2) Operational and Business Process Readiness, involving inventory management adaptation and strategic price-setting; (3) Payment Method Readiness, focusing on QRIS adoption, transaction cost incentives, and digital payment safety campaigns; (4) Knowledge and Institutional Readiness, encompassing structured financial literacy, community mentoring, government monitoring, and regulatory collaboration with fintech and key stakeholders. This study offers strategic policy recommendations to foster an inclusive and smooth transition for MSMEs during redenomination and digitalization. The proposed measures aim to optimize policy impact and practical readiness of business actors, thereby strengthening MSMEs’ role in supporting national economic growth.